LAZISMU Partnership Communication with Companies in the Implementation of Managing Corporate Social Responsibility Programs - Yulia Rahmawati; Farida Hariyati (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
Lembaga Amil Zakat Infak dan Shodaqoh Muhammadiyah (LAZISMU) is a national Obligatory charity foundation engaged in community empowerment. Furthermore, this foundation manages the charity and helps supervise the company's Corporate Social Responsibility. The implementation of the company's CSR with LAZISMU is related to the existence of a partnership, which is believed to be a solution for solving significant societal problems. Communication is influential in partnerships to reach the initial of the company. However, finding the meeting point among the organizations involved in the partnership is challenging, so it requires communication strategies to build sustainable partnerships. Therefore, This study aims to identify LAZISMU's partnership communication strategy with companies implementing CSR. Second, to find out the LAZISMU program ideas with companies in implementing CSR. The research method uses qualitative methods with a descriptive approach. The results of the study found that 1) Communication is a crucial factor in promoting the running of the partnerships, 2) LAZISMU's partnership communication strategy with companies prioritizes proactive engagement, 3) The implementation of CSR managed by LAZISMU includes education, health, economics, da'wah, social programs, and humanity.